Improving Students’ Ability To Describe in Speaking Competence By Using Note Card, Known As Cue Card - Fariani Siregar, Nelia (CV. Ridwan Publisher, 2020)
Speaking actually, is very important to be mastered because it can help us to communicate with others well. Speaking is used as a communicate tool to express the idea’s feeling, accept and transfer the information to other people. In another statement, it is the activity for sharing the information. Speaking enables students to receive information from people by their conversation. Based on preliminary research, the researcher found that there are some problems in speaking at Senior High School. Most of students are still afraid to speak English in front of the class because students are not confident to speak using English and they are lack of vocabulary. The students consider that English is a hard foreign language; they are fear of making mistakes, especially in Grammar. Thus, to make them have courage in speaking English, they need bugs motivation from the teacher. There are still many students asks question or answer teacher’s question by using first language (mother tongue) than using English. Most of students still feel anxious, shy and fear. This situation makes students have low achievement in speaking subject. Based on the brief explanation above, there are some problems in speaking. However, there is a way to solve the problems; one of way is using cue card as media in teaching speaking. Cue card is not something now in English teaching. Keywords: Cue Card, Speaking; Descriptive Text